Menulis Kajian Literatur - Amri - Marzali (ETNOSIA : Jurnal Etnografi Indonesia, 2016)
This article is part of lecture notes presented in the course of Qualitative Research Method, at The Graduate School of Universitas Muhammadiyah Prof. DR. HAMKA, 2016-2017 academic year. It is  written for students who precariously need a guidance to write a literature review for his or her scientific works (skripsi, tesis, and disertasi). Most parts of the paper comes from translation,  editing, and digesting of three resource books. This article will be divided into the following sections: What literature review is, aims of literature review, functions of literature review, ways of  using literature review, types of literature review, resources for writing literature review, procedures of writing of literature review, literature mapping for the research framework, writing an abstract, and writing a summary.